Acroski - en bedömningssport - Johansson, A.
In the field of sports results are of great importance. Results are the essence in competitive sports, and success or failure can change life overnight for elite athletes. This means that the quality of the measurements and judgements is an extremely important issue. The purpose of this report was to elucidate problems related to the validity and reliability of judgements in the freestyle skiing discipline, acroski. Reliability in the sense that different judges come up with exactly the same result for a certain freestyle skier, and, validity in the sense that the judgements, and the rules for the judgements are in accordance with the idea of the sport. Reliability in acroski depends partly on the ability of the judge to interpret the rules and, partly on the ability to make correct judgements based on these rules. Validity is concerned with the question whether the right things are judged. There is also dependence between reliability and validity. Individual, one-hour interviews were made with two judges, two coaches and four elite athletes. They came from four different countries and they all had a very long experience of acroski on the elite level. The information obtained from these interviews, together with the information about rules and changes in the rules over the years, were used as a basis for inferences about reliability and validity of the judgements in acroski. The main result of this study is that both the judging system and the content in the rules have gone through many changes during the past ten years and the conclusion is that the reliability as well as the validity of the judgements have increased.